Cation exchange membranes by radiation-induced graft copolymerization of styrene onto PFA copolymer films. III. Thermal stability of the membranes - Nasef, Mohamed Mahmoud; Saidi, Hamdani; Mohd. Nor, Hussin (John Wiley & Sons, 1999)
Thermal stability of cation exchange, PFA-g-polystyrene sulfonic acid membranes prepared by radiation-induced graft copolymerization of styrene onto PFA films followed by sulfonation was studied by thermal gravimetric analysis (TGA) and oven heat treatment. The tested samples included original and grafted PFA films as reference materials. All the membranes showed multistep decomposition patterns due to dehydration, desulfonation, dearomatization, and decomposition of the PFA matrix. Investigations of the individual decomposition behaviors showed that the weight loss strongly depends upon the degree of grafting. However, the decomposition temperatures were found to be independent of the degree of grafting. The loss in some selected membrane properties such as ion exchange capacity and water uptake was found to be function of the degree of grafting, temperature, and the time of heat treatment.